Estudo ab initio de materiais bidimensionais emergentes - Querne, Mateus Bazan Peters (2023)
Two-dimensional (2D) materials have attracted much attention in the last decade due to their unusual properties such as high degree of anisotropy and chemical flexibility. Since the isolation of a graphene layer, a wide variety of 2D materials have been reported in the literature, especially silicene and transition metal dichalcogenides. In particular, monochalcogenides and Janus demonstrate attractive properties for optoelectronic applications. Monochalcogenides are represented by the chemical formula MQ, where M is a chemical element from groups III-V (Al, Ga, In, Si, Ge, Sn, P, As and Sb) and Q is a chalcogen (S, Se and Te), while Janus are asymmetric structures that have characteristics on the sides of the layer of the material, i.e. SGeGeSe, SSnSnSe, SGeSnS and SeGeSnSe. In this work, the density functional theory (DFT) was applied through ab initio simulations to estimate the stability and the optoelectronic properties of these materials. Initially the mocochalcogenides of groups III-V were studied in structures based in 11 different space groups found in the literature. From these structures, an overview of the most stable structures for each composition, as well as the energetic and vibrational stability, in addition to the electronic properties of these materials, was provided. Group IV monochalcogenides aroused interest due to the competition between structures P-3m1 and Pmn2_1 for the energetic preference of the compounds. The structures Pmn2_1 were experimentally reported in the literature, however, we show that the structures P-3m1 are more stable and have optoelectronic properties different from the structures already reported. From structures P-3m1, Janus structures with internal and external asymmetry were generated. It was possible to analyze the energetic, dynamic and mechanical stability of these materials, in addition to being possible to identify the asymmetry through the Bader charge analysis.